O mito e a mídia: a imagem da ciência na revista Ciência Hoje das Crianças (2009-2010) - Sousa, Raquel Juliana Prado Leite de (2012)
This research analyses the scientific divulgation from children made by the Ciência Hoje das Crianças magazine, publication of Sociedade Brasileira para o Progresso da Ciência, in order to verify which science image is broadcasted by this publication, having a base of theoric framework in the field o f Science, Technology and Society (STS) and methodological conception of Content Analyses with qualitative approach. The aim of this research is to make an exploratory analysis of all the 2009 and 2010 editions in order to verify the presence or absence of scientific neutrality in the building the science image. It was used the categorization for collection by defining the categories of analyses a posteriori. The analyses which demonstrate the presence or absences of neutral scientific were raised, a) salvationism, b) superiority of techonocratical decision model, c) determinism, d) scientific controversial, e) research methodology, f) non-scientific knowledge (traditional, cultural, pop). It was realized that the univocal visions of science are predominant, the traditional knowledge appears in rare exceptions and the research results possesses the value of truth and superiority in favor of social wellbeing and technocracy. The research methodology inserts the notion that science is an observation process in constant construction; meanwhile there is absence of scientific controversies, except the fixed sections, it was verified that only 3.9% of the articles were signed by the editorial staff of the magazine; one of the articles appears unsigned. The authors of those reports and articles are generally from the states of Rio de Janeiro (41.04%), São Paulo (15.60%) and Minas Gerais (8.67%), which represents 65.31% of the total. The majority of quoted affiliations institutions are localized in the states of Rio de Janeiro (40.28%), São Paulo (15.64%) and Minas Gerais (10.20%). The most quoted institutions were Universidade Federal do Rio de Janeiro (12.04%), Universidade de São Paulo (12.04%), Universidade do Estado do Rio de Janeiro (11.44%), Universidade do Estado do Rio de Janeiro (11.44%), Universidade Brasília (4.81%) and Centro Federal de Educação Tecnológica de Minas Gerais (3.61%), which reveals that although the magazine is made for a notional range society, researchers and groups from Rio de Janeiro have the authorship predominance. Starting from hegemony of the Gramsci conception which the predominant class, or part of it, imposes her vision of the world promoting a cultural and ideological unification, we question which scientific culture has being disseminated in that publication, especially if you consider that Sociedade Brasileira para o Progresso da Ciência is a national range entity, which represents scientists from all Brazilian territory.